Effect of quercetin on the uptake and efflux of aristolochic acid I from Caco‐2 cell monolayers. (11th May 2016) - Kimura, Osamu; Fujii, Yukiko; Haraguchi, Koichi; Ohta, Chiho; Koga, Nobuyuki; Kato, Yoshihisa; Endo, Tetsuya
Abstract: Objective: The purpose of this study was to determine whether quercetin decreases the uptake of aristolochic acid I (AAI) from the apical membranes of Caco‐2 cells via H + ‐linked MCTs at neutral pH as well as to confirm the secretion of AAI through the Caco‐2 cell monolayers via ABC transporters. Methods: Caco‐2 cells cultured on the dishes or permeable membranes were incubated with AAI in the absence or presence of quercetin or transporter inhibitors. Key findings: Coincubation with quercetin decreased the uptake of AAI by Caco‐2 cells cultured on the dishes at pH 7.4, and a similar decrease in AAI uptake was found when the cells were coincubated with acetic acid or benzoic acid. In contrast, the basolateral‐to‐apical transport of AAI was higher than the apical‐to‐basolateral transport of AAI at pH 7.4, and the former transport was decreased by quercetin and the BCRP inhibitors of Ko‐143 and mitoxantrone, but not by P‐gp or MRP2 inhibitors. Conclusions: AAI appears to be secreted from the apical membranes of Caco‐2 cells via BCRP at neutral pH, although a small amount of AAI is taken up from the apical membranes via H + ‐linked MCTs, and quercetin may decrease both the BCRP‐mediated efflux and the MCT‐mediated influx of AAI.